Pemanfaatan Information System Jurusan TI-D3 Berbasis Web Pada Universitas Raharja - Gustina Gustina; Muhammad Khaidir Fahram; Alfarid Maulana Ependy (UNIVERSITAS RAHARJA, 2023)
With the rapid development of technology, especially in information technology, it has a positive impact on our lives as humans. Therefore, information processing must also be developed so that it is not out of date. Various technologies began to be applied to all daily needs. Throughout its development, Raharja University has become a flagship campus and Raharja University's mission is to be at the forefront of the field of information technology, so accurate and actual new innovations are needed. Along with the sophistication of digitization, one of the most appropriate information media today is the website. Because the website is a medium that can be accessed by anyone, anywhere, and anytime. The problem faced by the Head of the Diploma 3 Informatics Engineering Study Program (TI-D3) is that there is no main website that can provide information about the Study Program, so a scientific work is created which is expected to be a medium for delivering useful and useful information for Raharja University, especially Diploma 3 Informatics Engineering Study Program students (TI-D3) who have a concentration in Artificial Informatics and System Architecture. Keywords—Website, Technology, TI-D3 Department, UR Dengan berkembangnya teknologi yang semakin hari semakin pesat, terutama pada teknologi informasi membawa dampak positif dalam kehidupan kita sebagai manusia. Karena itu pengolahan informasi pun harus terus dikembangkan agar tidak ketinggalan zaman. Berbagai teknologi mulai diterapkan untuk segala keperluan sehari-hari. Sepanjang perkembangannya Universitas Raharja telah menjadi kampus Unggulan dan misi Universitas Raharja untuk menjadi yang terdepan dalam bidang ilmu teknologi informasi, maka diperlukan inovasi-inovasi baru yang akurat dan aktual. Seiring dengan canggihnya digitalisasi maka salah satu media informasi yang paling tepat saat ini adalah website. Karena website merupakan media yang dapat diakses oleh siapapun, dimanapun, dan kapanpun. Permasalahan yang dihadapi oleh Kepala Program Studi Teknik Informatika Diploma 3 (TI-D3) adalah belum adanya Website utama yang dapat memberikan informasi seputar Program Studi, maka diciptakanlah sebuah karya ilmiah yang diharapkan bisa menjadi media penyampaian informasi yang berguna dan bermanfaat bagi Universitas Raharja, khususnya mahasiswa-mahasiswa Program Studi Teknik Informatika Diploma 3 (TI-D3) yang memiliki konsentrasi Artifical Informatics dan System Architecture. Kata Kunci—Website, Teknologi, Jurusan TI-D3, UR